Seminal Fluid Analysis in Iraqi Fertile and Infertile Males Defined by the World Health Organization Criteria of 2010 - Kadri, Z. H. M.; Al-Assaf, A. I. S.; Ad'hiah, A. H.; Qassim, A. M.; Kadem, N. A.; Al-Salih, A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A total of 116 males with primary infertility and 32 fertile males (normozoospermia; NOR) were studied to evaluate parameters of seminal fluid analysis. Based on WHO criteria of 2010 for general seminal fluid analysis, the patients were distributed into three groups: 32 azoospermic (AZO), 40 oligozoospermic (OLI) and 44 asthenozoospermic (AST) patients. AZO and OLI patients and NOR shared an approximated mean of seminal fluid volume (2.25, 2.75 and 2.50 ml, respectively), while it was significantly increased (3.58 ml) in AST patients.In NOR men, the spermatozoa concentration was 65.13 x 106spermatozoa/ml, while it was significantly decreased in AST (51.42 x 106spermatozoa/ml) and OLI (5.58 x 106spermatozoa /ml) patients. The percentage frequency of progressive motility was significantly decreased in OLI and AST patients as compared to NOR (9.6 and 16.3, respectively vs. 50.6%). In contrast, the non-progressive motile (45.4 and 30.4, respectively vs. 21.9%) or immotile (45.0 and 52.5, respectively vs. 27.5%) spermatozoa were significantly increased in the patients. OLI and AST patients shared an approximated mean of abnormal spermatozoa frequency (56.7 and 58.3%, respectively), but both frequencies were significantly higher than the observed frequency in NOR (23.1%).